Isolation and diagnosis of the fungus Alternaria solani caused by early blight on tomatoes from different regions of Iraq (Journal of the College of Basic Education, 2024)
This study was conducted at the University of Baghdad / Faculty of Agricultural Engineering Sciences / Plant Protection Department / mycotoxin laboratory for the academic year 2019-2020, aiming to isolate and diagnose the fungus Alternaria solani caused by early blight disease in tomatoes under laboratory conditions .Solani was taken from tomato plants that showed signs and symptoms of the disease, where the isolates included different areas of Baghdad governorate (Nabai, Yusufiyah, Nahrawan, Abayji, Taji and Abu Ghraib) and were marked with symbols(C, E, N, A, T, A.D) successively, Salah al-Din governorate (Q), Karbala governorate (EF) and Basra governorate. (B) The results of electrophoresis on the acarose gel showed the presence of six clear bundles of six isolates of fungus A.solani (A.D ,B,C,EF,T, E) and the accompanying fungus Aspergillus sclerotiorum were boldly diagnosed with PCR technology. The result of doubling of these genes was shown when their molecular size was estimated at ~bp(545،548 ، 545 ، 539 ، 546، 541 ) the results of the sequences of natrogenic bases showed a 100% correspondence with the global isolates found in the NCBI global Genebank, and the nucleotide sequences of isolates were deposited in the Genebank under the accession numbers (MT199203.1, MT199327.1, MT199152.1, MT199337. 1, MT199154. 1 and MT199156. 1 for mushrooms A.solani respectively and the accession number of the companion fungus Aspergillus sclerotiorum which was first recorded in Iraq on a tomato plant is MT199218.1 . The results of microscopic examination of isolates showed the possibility of fungi to form a chain with a length of five spores, as indicated by the results of testing the pathogenicity of isolates in the Growth Index DSI (disease severity index), isolation E was characterized by giving an index of pathogenicity on tomato seeds, reaching 5, which means that isolation is highly pathogenic, followed by isolates N Q, ، EF ، A ، C ، T ، A.D, B if you have reached (4.25 ، 3.9 ، 3.69 ، 3.16 ، 2.43 ، 1.88 ، 1.58 ، 1.2 sequentially, the results of the growth index test on radish seeds also confirmed the superiority of the same isolation (E), giving the highest pathogenicity index of 5, followed by isolates Q, N, C, EF, A, T, A.D, B and B (4.12 ، 3.98 ، 3.81 ، 3.54 ، 3.28 ، 2.85 ، 2.71 ، 1.76 ) the laboratory results showed the ability of all isolates to significantly reduce the percentage of germination of tomato and radish seeds on PDA compared to the comparative treatment, where isolation E gave the lowest germination percentage of tomato and radish seeds, reaching 00% and 00% sequentially, and isolation A gave.D the highest percentage The percentage of germination compared to isolates, but it caused a significant decrease with the comparison treatment, as it reached 33.33 and 38.33 respectively, while the percentage of comparison for tomato and radish seeds reached 100%and 100%